EPIDEMIOLOGY OF DIPHTERIA IN PURWAKARTA REGENCY INDONESIA - Wijayanti, Siwi Pramatama Mars; Fadillah, Alfianti Nur (Epidemiology and Society Health Review (ESHR), 2019)
Background: Diphtheria is considered as a neglected disease since it was successfully eliminated in many countries. However, there were several sporadic re-emergence cases of Diphtheria and the peak was outbreak in Indonesia in 2017.Â  This research was a descriptive study aimed to explore epidemiology of diphtheria by person, time and place in one of diphtheria endemic area.Methods: This was a descriptive study with cross sectional design in Purwakarta Regency, West Java, Indonesia in 2018. Several data were collected in this study such as diphtheria cases by age, time of occurrence, gender, place and immunization status. The data was collected from Purwakarta Health Office. It was the data from the year of 2015-2017. The data was analysed by using descriptive analysis with percentages displayed in graphs and tables.Results: This study reveals that Purwakarta regency is an endemic area of diphtheria with fluctuated cases since 2015-2017. More cases of diphtheria occurred from September to December in rainy season. More cases suffered by children in 5-9 years old, however, this disease also infected adult population. The area with high diphtheria cases in this study also areas with high population densities which is conducive for C diphteriae transmission. Low coverage of immunization is highlighted in the result of this study, which could explain why diphtheria cases occurred continuously in this area.Conclusions: High number of diphtherias in this area should be an awareness for local health officer to do an effective preventive effort such as increasing the coverage of vaccination. Furthermore, optimizing the role of religious and community leader should be made to support diphtheria vaccination programs.